Cortical spreading depression and translational mechanisms in migraine headache - Moskowitz, Michael (Henry Stewart Talks, 2009)
Migraine headache, Pathophysiology and importance of cortical spreading depression (CSD), Evidence for CSD in human cortex, Susceptibility to CSD as modified by genetic mutations, Susceptibility to CSD as modified by ovarian hormones, Prophylactic drugs render the brain resistant to CSD, Hypoxia insult during the propagation of CSD